Response of two high yielding Hevea clones to applied fertilizers during immature phase - George S; George E S; Jessey M D; Mani J; Mathew M; Pothen J; Punnoose K I (Indian Journal of Natural Rubber Research, 1997)
The results of a 3 3 factorial experiment conducted at two locations with two high yielding clones (RRII 105 and PB 235) of Hevea brasiliensis are discussed in relation to growth and soil fertility characteristics. Application of N, P2O5 and K2O at the rate of 30, 30 and 20 kg per ha respectively resulted in significant increase in girth and girth increment in both clones. Clone PB 235 responded to the application of fertilizers during the entire period of immaturity, whereas RRII 105 responded only during the early immaturity period.
Keywords: Fertilizer response; Fertilizer response; Growth; Growth; Hevea; Hevea; Immaturity period; Immaturity period; Tappability; Tappability